The body in everyday life - Nettleton, Sarah, 1960-; Watson, Jonathan, 1960- (Routledge, 1998)
We all have a body, but how does it impact upon our everyday life? This new and accessible introduction to the sociology of the body explores how ordinary women, men and children talk about their bodies.